Teaching parametricism as a standard skill for architecture - Riekstins, Arne (Journal of Architecture and Urbanism, 2018)
The traditional need for coding to create parametric design has become quite obsolete with the advent of powerful visual programming languages for most becoming architects of the current young generation that are studying all around the world. Parametricism might become one of the standard skills for applicants seeking for a position at architectural design practices. It raises a question – how to implement the parametric knowledge into the workflow of a classical architectural designing approach, and rethinking the way we present these concepts at university level education of architecture. Additional knowledge of subjects is necessary, for example, about the structural integrity, material tolerance, fabrication optimization, sustainability issues etc. just to name the most frequent areas where lies the highest potential of making mistakes when these new systems are in use. Meanwhile the CAD/CAM paradigm that let architects design straight for fabrication brings new challenge for construction practice. Parametricism is an excellent platform of research for form finding, as there is very little amount of time needed to recreate significantly different design proposals by changing the variables, as soon as the bigger system of internal relations is set up.